Development to Marketing innovation to create competitive advantage in textiles and apparel in Thailand - Hemtanon, Thongchai (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This study aimed to 1) study the influence of marketing innovationtoward the increasing of value to increase competitive advantage on textile andgarment businesses 2) analyze the matching of marketing innovation structure with the of increasing value to increase competitive advantage on textile and garment businesses 3) specify the marketing innovation structure and the increasing value which influenced the increasing of competitive advantage on textile and garment business. The finding results were as the following: 1. The marketing innovation and increasing value showed causal relationship with statistically significant different at 0.05 (p<0.05). The positive relationship with path coefficient was at 0.810. Regarding the efficiency of forecasting. It was found that causal relationship model related to marketing innovation and increasing value, which influenced the increasing competitive advantage on textile and garment businesses. 2. Marketing innovation had causal relationship with increasing competitive advantages. With statistically significant different at 0.05 (p<0.05) each of which had positive relationship with path coefficient at .927. In addition, the increasing value had causal relationship with the increasing competitive advantages with had path coefficient at 0.924 The efficiency of forecasting, found that causal relationship model related to marketing innovation and increasing value, which influenced to increasing of competitive advantage. Article history : Accepted 27 October 2015 SIMILARITY INDEX = 2.08